Pengaruh Learning Approach terhadap Prestasi Belajar pada Mahasiswa Fakultas Teknik Perguruan Tinggi Swasta di Bandung - Gany, Audyati (Zenit, 2015)
This research was conducted to determine the effect on Learning Approach toward theLearning Achievement of Engineeringâs students at one of the private Universities in Bandung, whotook the course in Rangkaian Listrik I on February – June 2013. The population of students who tookcourses in Rangkaian Listrik I on February – June 2013 are 110 students, and the sample used are 98students.The design used in this study is a correlation research design. Measuring instruments used inthis study based on Learning Approach measuring instrument which is a translation of the RevisedTwo-Factor Study Process Questinnaire (R-SPQ-2F), which consists of 20 items. Validity of measuring instrument have ranges 0.304–0.557, reliability is 0.816. Measuring instruments used to measure learning achievement is the quality of the course grades Rangkaian Listrik I. The dataobtained were processed and tested by the method of Pearson product moment correlation coefficient using SPSS 17.0.The conclusion is a weak influence on Learning Approach of the Learning Achievement.Suggestions for further research, testing can be performed on other factors of learning achievements, and can be done in a course of study in the field of Social or Science.Keywords: Learning Achievement, Learning Approach